Employee Performance at PT. Maleo Technology Education: The Impact of Work Stress and Environment (Educourse.id) - Fortuna, Aurelia Tari; Nugroho, Rusdi Hidayat (Jurnal Manajemen (Edisi Elektronik), 2024)
PT. Maleo Edukasi Teknologi recognizes HR's vital role amid business changes, offering STEAM-based education for Industry 4.0 skills in Indonesia. This study, with 40 employees, delves into the impacts of Responsibility, Work Pressure, and Workplace in a challenging environment at PT. Maleo Edukasi Teknologi (Educourse.id). Quantitative methods were used, sampling all 40 employees, gathering data through polls, and employing SPSS 25 for statistical analysis. Linear regression assessed each independent variable's total and partial effects on the dependent variable. Result and Discussion: Work Stress negatively and significantly impacts employee performance (tcount-3.644 > ttable 2.028, significance 0.001). Work Environment has a negative impact tcount -0.439 Ftable 3.25 and significance 0.000. Conclusion: In conclusion, the workplace has a positive but non-significant impact, while work pressure negatively affects representation implementation. Overall, Responsibility, Work Pressure, and Workplace collectively positively influence PT. Maleo Edukasi Teknologi (Educourse.id).